Kepribadian Tokoh Lucas Ford dalam Novel In A Blue Moon Karya Ilana Tan: Kajian Psikologi Sastra - Mutik Sirait, Raisyicha; Marsella, Emma; Riyanto, Bambang (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research specifically aims to describe the personality structure and personality of the character Lucas Ford in the novel In a Blue Moon by Ilana Tan. This research uses a qualitative approach with descriptive methods. This type of research uses a qualitative research method with a descriptive method, which collects and analyzes scientific data and then describes the facts in detail to determine the personality structure and personality of the character Lucas Ford in the novel In a Blue Moon by Ilana Tan. The research studied is the personality structure and personalities of characters in literary works. This approach will provide an overview of the thought processes experienced by Lucas Ford in the form of id, ego, and superego personality structures, and in the form of choleric, melanchole, phlegma, and sanguine personalities. The results of the research show that Lucas Ford's personality structure in the novel In a Blue Moon Ilana Tan's work is Lucas Ford's id which tries to find pleasure, the ego which adheres to the principles of reality and reality while the superego tries to understand the needs of the id and ego. Lucas Ford's personality in the novel In a Blue Moon by Ilana Tan is the more prominent of the four personalities, namely choleric (choleric). Lucas Ford's personality is wise, focused on goals, confident, firm, flammable, brave and honest. The choleric personality also has ego and superego personality structures.